Suicide in DSM-5: Current Evidence for the Proposed Suicide Behavior Disorder and Other Possible Improvements - Fehling, Kara B.; Selby, Edward A. (Frontiers in Psychiatry, 2021)
Suicide continues to be one of the greatest challenges faced by mental health clinicians and researchers, an issue made worse by increasing trends in the global suicide rate (Naghavi, 2019). Suicide behavior disorder (SBD) was introduced in DSM-5 (APA, 2013) as a disorder for further consideration and potential acceptance into the diagnostic system. There are numerous positive developments that would arise from the addition of a suicide-related diagnosis. Utilizing the guidelines established by Kendler and colleagues (2009), the present review examines the evidence for SBD’s validity and discusses the diagnosis’ potential clinical benefits and limitations. Altogether, growing evidence indicates that SBD has preliminary validity and benefit. SBD presents with several significant limitations, however, and possible alternative additions to future DSMs are highlighted.